Diffusion of the SILETON Application in Strengthening Smart Governance in Agam Regency's Population Services - Mutia Kardina; Aldri Frinaldi (Publica: Jurnal Pemikiran Administrasi Negara, 2025)
The development of information and communication technology drives the transformation of public services towards a more efficient, transparent, and participatory digital direction. The Agam Regency Government responded to this change by presenting the SILETON (Integrated Online Electronic Service System) application as an innovation in population administration services. However, in the implementation process, various obstacles were still found, such as low digital literacy of the community, limited technological infrastructure, and uneven levels of service adoption. This study aims to analyze the process of innovation diffusion of the SILETON application based on Everett Rogers' Diffusion of Innovation theory, assess its contribution to the implementation of smart governance, and formulate strategies for optimizing digital-based services at the regional level. The method used in this study is a descriptive qualitative approach, with data collection techniques in the form of in-depth interviews, observation, and documentation. Informants were selected purposively involving the Agam Regency Population and Civil Registry Office, application managers, and user communities. The results of the study show that the SILETON innovation diffusion process has shown significant progress, but is not evenly distributed across all levels of society. This application contributes to increasing transparency, efficiency, and public participation as characteristics of smart governance. Suggested optimization strategies include increasing digital literacy, strengthening network infrastructure, developing user-friendly application features, and active collaboration between agencies. These findings emphasize the importance of a holistic approach in driving the success of digital innovation in local government to create more inclusive and adaptive public services.